Lecture des coalitions dans un lycée par la sémiotique situationnelle - Lambert Lipoubou (Communication)
This is a case study of an altercation, in a classroom, between a teacher of health and social sciences and technologies and a student in her final year. The author applies the semiotic theory of Alex Mucchielli and focuses on how those involved in the altercation construct meaning out of the situation. This is a case study in the phenomenology of conflict.